PHYTOCHEMICAL SCREENING AND ANTIBACTERIAL ACTIVITY OF SOFT CORAL Nephthea sp. EXTRACT ISOLATED AGAINST Escherichia coli - Setyaningrum, Tri Wahyu; Nurulfadilah; Candri, Dining Aidil; Dharmayani, Ni Komang Tri; Ghazali, Mursal; Faturrahman (BIOMA : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the antibacterial potential of Nephthea sp. extract against Escherichia coli and to analyze the phytochemical constituents present in Nephthea sp. using various solvents. The extraction process was carried out using the maceration method with three different solvents: n-hexane, ethyl acetate, and methanol. The resulting extracts were analyzed through phytochemical screening and antibacterial activity assays. The results showed that Nephthea sp. extract contained several classes of bioactive metabolites, including alkaloids, flavonoids, triterpenoids, steroids, tannins, and saponins. Antibacterial testing demonstrated that the ethyl acetate extract produced the largest inhibition zone, measuring 3.16 mm. Based on the ANOVA test results, the 25% concentration showed a significant effect on the inhibition zone. Based on phytochemical analysis, the ethyl acetate extract contained triterpenoid compounds, whereas the other solvents did not